Costs and Benefits of an Organized Fecal Immunochemical Test-Based Colorectal Cancer Screening Program in the United States - Guy, Gery P. (Cancer, 2014)
BACKGROUND: Despite clear recommendations and evidence linking colorectal cancer screening to lower incidence and mortality, >40% of adults are not up to date with screening. Existing domestic and international models of organized cancer screening programs have been effective in increasing screening rates. Implementing an organized, evidence-based, national screening program may be an effective approach to increasing screening rates. METHODS: In the current study, the authors estimated the initial investment required and the cost per person screened of a nationwide fecal immunochemical test (FIT)-based colorectal cancer screening program among adults aged 50 years to 75 years. RESULTS: The initial additional investment required was estimated at $277.9 to $318.2 million annually, with an estimated 8.7 to 9.4 million individuals screened at a cost of $32 to $39 per person screened. The program was estimated to prevent 2900 to 3100 deaths annually. CONCLUSIONS: The results of the current study indicate that implementing a national screening program would make a substantial public health impact at a moderate cost per person screened. Results from this analysis may provide useful information for understanding the public health benefit of an organized screening delivery system and the potential resources required to implement a nationwide colorectal cancer screening program, and help guide decisions about program planning, design, and implementation.